2007
DOI: 10.1097/ta.0b013e31802dd712
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production in Lipopolysaccharide-exposed Rat Lung Pericytes

Abstract: Pericytes contain the machinery necessary, and produce pro-inflammatory cytokines. Cocultures manufacture less IL-1B then pericytes alone, which is similar to previous coculture observations. Pericyte activation and cytokine production may play a role in capillary leak seen in gram-negative sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
1
29
0
Order By: Relevance
“…Reduction of NF-κB, ERK1/2 and JNK activation in adipose tissue of rAd-GLP-1-treated mice Activation of NF-κB is involved mainly in the expression of inflammatory responsive genes such as Il6 and Tnfa [20,21]. As pro-inflammatory cytokine production is reduced by rAd-GLP-1 treatment, we used EMSA to examine the activation of NF-κB in epididymal fat at 2 weeks after rAd-GLP-1 treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of NF-κB, ERK1/2 and JNK activation in adipose tissue of rAd-GLP-1-treated mice Activation of NF-κB is involved mainly in the expression of inflammatory responsive genes such as Il6 and Tnfa [20,21]. As pro-inflammatory cytokine production is reduced by rAd-GLP-1 treatment, we used EMSA to examine the activation of NF-κB in epididymal fat at 2 weeks after rAd-GLP-1 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…4a). Because ERK1/2 and JNK are involved in NF-κB activation [21][22][23], we examined the activation of ERK1/2 and JNK in epididymal fat by western blot. We found that phosphorylation of ERK1/2 and JNK was decreased in rAd-GLP-1-treated ob/ob mice compared with untreated, rAd-βgal-treated and pair-fed ob/ob mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The significance of pericytes in the regulation of T cell responses is further strengthened from observations that immunomodulatory cytokines/growth factors and adhesion molecules may be secreted or elaborated from pericytes under certain conditions (17)(18)(19). Recently, elegant work by Stark et al (20) established the instructive role of NG2 + pericytes on innate myeloid leukocytes for their homing into sites of inflammation as a consequence of upregulating ICAM-1 expression and macrophage migration inhibitory factor-mediated signaling.…”
mentioning
confidence: 99%
“…In a series of pioneering works by Edelman et al (13)(14)(15), the authors demonstrated the expression of TLR4 by Western blotting in rat lung pericytes (13) as well as increased vessel permeability (14) and production of IL-1␤ (15) in LPS-treated pericytes, suggesting for the first time an active role of pericytes in the inflammatory cascade. More recently, the release of nitric oxide and several cytokines and chemokines by mouse brain vascular pericytes in response to LPS has been reported (16).…”
mentioning
confidence: 99%